Training Program for MSME Owners: A Needs Assessment - Bongalonta, Michael B.; Bongalonta, Michelle M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The purpose of this study was to evaluate the MSME Owners in Sorsogon's present skill and competency levels as well as their need for training programs. Additionally, this needs assessment identifies particular talents that are thought to be crucial to improving business operations. This study will identify the MSME Owners' profile with regard to training program accessibility.   The study's findings suggest that MSME owners needed specialized training programs to improve their skills, creativity, and long-term performance in this changing economic climate. Due to time and cost constraints, MSME owners have limited access to trainings; therefore, this program will help them stay current on industry developments and be of tremendous advantage to them. It is strongly advised that MSME owners attend trainings.